A novel quasi-dynamic guidance law for a dynamic dual-spin projectile with non-conventional, asymmetric roll constraints - Norris, James; Economou, John T.; Hameed, Amer (Sage, 2022)
A novel quasi-dynamic guidance law (QDGL) is presented for a dual-spin projectile (DSP) with unconventional constraints on roll direction. A 7 degree-of-freedom (DOF) dynamic model is established and the projectile operational mechanism is presented with a description of how it is used to enact control. The QDGL is presented and a parametric study is conducted to show how the QDGL parameters affect the system response. A procedure of using batches of Monte Carlo simulations is described, to numerically compare the system response with different QDGL configurations. A genetic algorithm is then used to optimise both the innate system parameters and PID controller gains. The disturbance rejection capabilities of the optimal QDGL are then evaluated along with the performance against different target profiles. It was found that the GA optimised QDGL is able to provide satisfactory control capabilities against static and dynamic targets.
Keywords: Guidance law; dual-spin; projectile; genetic algorithm